Study of (AgxCu1−x)2ZnSn(S, Se)4 monograins synthesized by molten salt method for solar cell applications. (1st March 2020) - Oueslati, S.; Kauk-Kuusik, M.; Neubauer, C.; Mikli, V.; Meissner, D.; Brammertz, G.; Vermang, B.; Krustok, J.; Grossberg, M.
Highlights: Single phase (Agx Cu1−x )2 ZnSn(S, Se)4 monograins were synthesized in molten flux. Adding Ag to CZTSSe increases carrier concentration and decreases carrier lifetime. Low Ag contents (x ≤ 0.02) in CZTSSe lead to higher solar cell device efficiencies. The Ag incorporation changed the dominant radiative recombination channel in CZTSSe. The Ag incorporation decreased the collection width as evaluated by the EBIC study. Abstract: The open circuit voltage (VOC ) deficit of Cu2 ZnSn(S, Se)4 (CZTSSe) kesterite solar cells is higher than that of the closely related Cu(InGa)Se2 solar cells. One of the most promising strategies to overcome the large VOC deficit of kesterite solar cells is by reducing the recombination losses through appropriate cation substitution. In fact, replacing totally or partially Zn or Cu by an element with larger covalent radius one can significantly reduce the concentration of I–II antisite defects in the bulk. In this study, an investigation of the impact of partial substitution of Cu by Ag in CZTSSe solid solution monograins is presented. A detailed photoluminescence study is conducted on Ag-incorporated CZTSSe monograins and a radiative recombination model is proposed. The composition and structural quality of the monograins in dependence of the added Ag amount are characterized using Energy Dispersive X-ray Spectroscopy and X-Ray Diffraction method, respectively. The Ag-incorporated CZTSSe monograin solar cells are characterized by temperature dependent current-voltage and electron beam induced current methods. It was found, that low Ag contents (x ≤ 0.02) in CZTSSe lead to higher solar cell device efficiencies.